Much ado about a latte [large type] - Fuller, Kathleen (A Maple Falls Romance, 2022)
"Anita Bedford needs to face reality. It's time to decaffeinate the dream that she and Tanner will ever be more than friends. Growing up in small-town Maple Falls, she's had a crush on Tanner for years. But he'll only ever see her as good, old, dependable Anita. Now she's finally ready to make her own goals a reality. In fact, that deserted building next door to Sunshine Diner looks like a promising location to open her own caf̌. Tanner Castillo may know how to operate a diner, but he doesn't know beans about love. After pouring his life savings into buying Sunshine Diner, he needs to keep his mind on making a success of it and supporting his widowed mother, not on kissing Anita Bedford. First order of business: improve his customers' coffee experience. Then he should probably find out who bought the building next door ... It's a bitter cup to swallow when ambition turns longtime friends and coworkers Anita and Tanner into rivals. Now that they own competing businesses, how could they ever compete for each other's hearts? Or will the two of them come to see what's obvious to the whole, quirky town of Maple Falls: potential for a full-roast romance, with an extra splash of dream? Welcome to Maple Falls, where everyone knows your name and has thoughts on your love life"--